Government fragmentation and educational outcomes: Evidence on the creation of municipalities in Chile - Manuel Alcaíno; Analía Jaimovich; Carolina Méndez; Diana Vásquez (Inter-American Development Bank (IDB), 2022)
We explore how government fragmentation affects public education provision by examining the case of Chile, which created 11 municipalities between 1994 and 2004. Using territories that sought, but failed to, achieve independence as controls, we find that schools in newly created municipalities, on average, experienced a standard deviation decline of 0.2 in elementary school mathematics performance. In addition, fragmentation led to a high turnover and increased job insecurity of classroom teachers and school management teams in newly created municipalities. In contrast, we found that reducing the size of the original municipalities school networks does not impact student outcomes or school personnel. Overall, our findings point to specific unintended educational effects of policies that seek to enhance horizontal decentralization.
Keywords: I21; I28; H83; 330; Municipalities; Decentralization; Education; Chile